Quantitative analysis of motifs contributing to the interaction between PLS‐subfamily members and their target RNA sequences in plastid RNA editing. (6th November 2014) - Okuda, Kenji; Shoki, Harumi; Arai, Miho; Shikanai, Toshiharu; Small, Ian; Nakamura, Takahiro
Summary In plant organelles, RNA editing alters specific cytidine residues to uridine in transcripts. Target cytidines are specifically recognized by pentatricopeptide repeat (PPR) proteins of the PLS subfamily, which have additional C‐terminal E or E‐DYW motifs. Recent in silico analysis proposed a model for site recognition by PLS‐subfamily PPR proteins, with a correspondence of one PPR motif to one nucleotide, and with the C‐terminal last S motif aligning with the nucleotide at position –4 with respect to the editing site. Here, we present quantitative biochemical data on site recognition by four PLS‐subfamily proteins: CRR28 and OTP85 are DYW‐class members, whereas CRR21 and OTP80 are E‐class members. The minimal RNA segments required for high‐affinity binding by these PPR proteins were experimentally determined. The results were generally consistent with the in silico‐based model; however, we clarified that several PPR motifs, including the C‐terminal L2 and S motifs of CRR21 and OTP80, are dispensable for the RNA binding, suggesting distinct contributions of each PPR motif to site recognition. We also demonstrate that the DYW motif interacts with the target C and its 5′ proximal region (from −3 to 0), whereas the E motif is not involved in binding.